The influence of thermomechanical coupling on the behaviour of athick-walled metallic tube subjected to internal pressure - Śloderbach, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
In this study, the influence of thermomechanical coupling effect - the effect of thermal expansion due to dissipation of the energy of plastic deformation, with and without taking into account the stored energy of plastic deformation (SEPD) for the distribution of stresses, strains, temperature, the applied pressure and the residual stresses is examined.
Keywords: thick-walled tube; thermomechanical coupling; actual stresses; residual stresses; strain; pressure